Revealing lactylation-mediated mechanisms and hub genes in heart failure pathogenesis - Xie, Hongguang; Wang, Yiqiang; Zhu, Xing; Zhang, Lili; Niu, Heli; Jin, Hongguang (Frontiers in Cardiovascular Medicine, 2025)
PurposeThis study explores lactylation's pivotal role in the disease progression of heart failure (HF).MethodsThe GSE57345 dataset, encompassing 177 HF samples and 136 normal controls (CTL), was sourced from Gene Expression Omnibus (GEO). Differentially expressed genes between HF and CTL groups underwent enrichment analysis using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Weighted correlation network analysis (WGCNA) and unsupervised clustering were employed to identify HF-associated gene modules and subtypes, and these were intersected with lactate-related genes (LRGs), curated from the Molecular Signatures Database and GeneCards, to pinpoint hub genes implicated in lactylation-mediated HF (Lcy-HF). The least absolute shrinkage and selection operator (LASSO), XGBoost, Boruta algorithm, and protein–protein interaction (PPI) networks were utilized to identify these hub genes. The diagnostic potential and biological significance of these hub genes in HF progression were assessed using receiver operating characteristic (ROC) curves, gene set enrichment analysis (GSEA), and immune infiltration analysis.ResultsIn the comparison between HF and CTL samples, 91 upregulated and 88 downregulated genes were identified, primarily enriched in inflammatory responses and pathways. By intersecting 387 LRGs curated from databases, we pinpointed six hub genes implicated in Lcy-HF: GATA2, HBB, JAK2, STAT2, STAT4, and WARS2. Immune infiltration analysis further revealed that these Lcy-HF hub genes are associated with macrophage polarization.ConclusionsLactylation plays a crucial role in the pathogenesis of HF, with genes such as GATA2, HBB, JAK2, STAT2, STAT4, and WARS2 emerging as potential lactylation biomarkers for HF identification. The lactylation-macrophage polarization–inflammation axis stands out as a pivotal mechanism driving HF progression.